Trends of cause-specific cardiovascular disease mortality in China, 2009-2019: a nationwide longitudinal study - Lu Wang; Yuzhu Wang; Zixiang Ji; Rongyu Zhu; Hengjing Wu; Jue Li; Liang Zheng; Lijuan Zhang (Annals of Medicine)
Background Cardiovascular disease (CVD) is the top cause of death in China. We aimed to identify trends in cause-specific CVD mortality in a rapidly developing country, thereby providing evidence for CVD prophylaxis.Materials and Methods Using raw data from the Chinese National Mortality Surveillance (CNMS) system, we assessed the mortalities of all CVD and cause-specific CVD during 2009-2019. Temporal trends of crude mortality rates (CMRs) and age-standardized mortality (ASMRs) of CVD were evaluated using joinpoint regression models. Age-sex-specific CVD mortality rates were predicted by using age-period-cohort Poisson regression model.Results A total of 10,608,402 CVD death occurred during 2009-2019, accounting for 49.8% of all-cause of death in China. The three major CVD types [cerebrovascular disease, ischemic heart disease (IHD) and hypertensive disease (HD)] accounted for 94.6% of total CVD deaths. The CMR of all CVD increased [the annual average percentage change (AAPC) = 3.4%, 95% confidence interval (CI) 2.6% to 4.1%] while the ASMR decreased (AAPC = −2.0%, 95% CI −3.5% to −0.6%). Cerebrovascular disease is predicted to be the leading cause of CVD death in men and IHD will be the top cause of CVD death in women over the period 2025-2029.Conclusions Although the ASMR of total CVD decreased, CVD remained the leading cause of death in China. Cerebrovascular disease, IHD and HD were the major three leading causes of CVD-related death. Inflammatory heart disease-associated death increased in the young population. Attention should be paid to premature deaths associated with cerebrovascular disease and rheumatic heart disease among rural residents.